Museums and Education: Theoretical Approaches and Implications for Asian Universities - Badrul Isa; Zuraimi Zakaria (UiTM Publisher, 2007)
Over the last few decades, museums have become centres of learning and not merely places for the exhibition of artefacts. Learning is a process based on knowledge and is not necessarily confined to classrooms. Children learn best through visual interaction and learning through the visual medium is considered to be more effective than learning through texts. In museums, visitors interact with visual objects leading to a more meaningful learning process. Children are especially fascinated with the objects displayed, which can become an effective medium of instruction. This article discusses educational and psychological theories and empirical studies that could be employed by museum educators to facilitate effective museum learning. In addition to teaching approaches, this article also discusses the possibility for university teaching and learning experience to be gained at museums and art galleries as part of training requirements for students undertaking Art and Design courses as well as Visual Art Education courses in Asian universities.